Vilnius in the Russian Poems of its Poets - Brio, Valentina (Literatūra, 2025)
This article-essay deals with the image of Vilnius captured in Russian poems by poets who live (or lived) in the city. The material for the essay is drawn from poems published in the book “The Call of Vilna. The Poetic Image of Vilnius”, published in Vilnius in 2017. We focus on a small part of the anthology, specifically, poems from the last decades of the 20th and the initial decades of the 21st centuries. In poetic depictions of the city – travelogues containing recollections of its historical past, ekphrases inspired by old postcards or photographs – abundant intertextual connections can be observed. The image of Vilnius is to a large extent romanticized; sacred motifs occupy an important place in the poetic topos of the city, as do numerous mythological images and legendary plots. Many poems tell of the ‘lost world’ of the city – its destroyed Jewish communities, with the lyrical subject wandering through the Jewish quarters of Vilnius as though moving through a space of memory. Not all the poems collected in the anthology are professional in form, yet almost every poem is imbued with genuine love for the city.